Nutritional Supplementation to Increase Influenza Vaccine Response in Children Living With HIV: A Pilot Clinical Trial - Talía Sainz; Talía Sainz; Talía Sainz; Inmaculada Casas; Inmaculada Casas; Mónica González-Esguevillas; Luis Escosa-Garcia; Luis Escosa-Garcia; Luis Escosa-Garcia; María Ángeles Muñoz-Fernández; María Ángeles Muñoz-Fernández; Luis Prieto; et al. (Frontiers Media S.A., 2022)
AimsVaccine response is poor among children living with HIV. The gut microbiota has been identified as a potential target to improve vaccine immunogenicity, but data are scarce in the context of HIV infection.MethodsPilot, double-blind, randomized placebo-controlled trial in which 24 HIV-infected children were randomized to receive a mixture of symbiotics, omega-3/6 fatty acids, and amino acids or placebo for 4 weeks, each in combination with ART, and were then immunized against influenza. Vaccine response and safety of the nutritional supplementation were the primary outcomes.ResultsEighteen HIV-infected children completed the follow-up period (mean age 11.5 ± 4.14 years, 61% female). The nutritional supplement was safe but did not enhance the response to the influenza vaccine. A 4-fold rise in antibody titers was obtained in only 37.5% of participants in the intervention arm vs. 40% in the placebo. No immunological or inflammatory predictors of vaccine response were identified.ConclusionsIn this exploratory study, a 4-week course of symbiotics did not increase influenza vaccine immunogenicity in HIV-infected children. Larger studies are warranted to address the potential of modulating the microbiome in children living with HIV.